MEWUJUDKAN EKOLOGI INTEGRAL DALAM KEHIDUPAN KELUARGA SEBAGAI WUJUD PERTOBATAN EKOLOGIS BERDASARKAN ENSIKLIK LAUDATO SI’ DI PAROKI SANTO YOSEF LAWE DESKY - Margareth Santa Elisabet Br Hutabarat; Paulinus Tibo (Jurnal Masalah Pastoral, 2026)
The This study aims to describe the discourse of integral ecology and the praxis of ecological conversion within families at Saint Joseph Parish, Lawe Desky, in light of the Encyclical Laudato Si’. Ecological crises in agrarian regions are often triggered by the tension between economic necessity and environmental preservation, requiring a theological-practical review at the grassroots level. Employing a descriptive qualitative method, data were gathered through observation and in-depth interviews with seven lay families, the Parish Pastoral Council (DPPH), and the Parish Priest. The results reveal a “cognitive anomaly”, where the faithful are unfamiliar with the technical terminology of Laudato Si’, yet substantially embody the values of stewardship through an existential awareness of human dependence on nature. The praxis of ecological conversion manifests in microscopic actions within the Ecclesia Domestica, such as disciplined waste management and intergenerational ecological education. Nevertheless, structural hurdles persist, particularly the economic dependence on the corn farming sector, which poses risks of forest degradation. This research concludes that sustainable ecological conversion in Lawe Desky requires an integration of spiritual faith and the transformation of agricultural techniques aligned with nature.